SEMANTIC APPROACH TO THE TURKISH SHAMANIC COSTUMES - Sibel KILIÇ (Zeitschrift für die Welt der Türken, 2010)
Siberian region being within Russian borders is host to important Shaman data from past to this date, and forms the most important region for the “Turkish Shamanism”. The subject under examination addresses main design types that reflect the style of the region and among many tribes; those which had been selected are qualified within Turkish Shaman cultural criterion and they had been limited to some major tribes which are: Altai, Yakut, Hakas, Tuva, Tofa and Dolgan tribes. The Shaman clothing which passes from father to son through inheritance or “Call Method” has been considered a form of sacred cult articles which were accepted as cosmic accessories that would transfer one into another universe which in turn has separated the owner from the rest of the members of the community and became the symbol of their isolated lifestyle. Almost all decorative elements of their clothing are consist of either aerial animals “Birds” sometimes ground animals such as deer, moos or Bear. However, it is possible to come across Shaman clothes designs which depict both aerial and ground animals together which form the basis of the oldest Turkic Shaman costumes. Style and design have been noticed as different concepts in Shaman costumes which form a religious cosmography when stood alone. As style is to do with “expression” side of the shaman’s dress, design is related to “the form” of it. Based on this, style is developed in a way which is in symbolic expression of shamanic person these are shapes of aerial and ground animals. However, the design reflects the signs of modification either on the basis of functionality or meaning throughout the time due to interaction. New forms being added and new designs being made indicates us the national development of system of shamanism. Shamanism that still has been on the forefront of a debate whether it is a religion or not, under oppression of other religions, shamanic costumes also have been influenced by cultural corruption which was seen almost in every society by significantly deviating from their traditions, in comparison to the past they have lost their authenticity and importance.